Construção e análise psicométrica de um inventário de habilidades sociais para cuidadores de idosos familiares - Pinto, Francine Náthalie Ferraresi Rodrigues (Universidade Federal de São Carlos, 2016)
With the rise in life expectancy and the high incidence of chronic degenerative diseases among the elderly, there is a growing demand to dedicate time to caring for an elderly family member. Caring for a dependent elderly person requires the acquisition of skills that are specific to this context, such as social skills (SS), which affect the wellbeing of the caregiver and the elderly care recipient. Given the situation-dependent nature of SS, it is important to be able to identify deficits in caregivers’ SS, but no instruments for evaluating SS in this population were found. Thus, the aim of this thesis was to develop an inventory of social skills for family caregivers of the elderly, and to analyze its psychometric properties. A review of the literature on the use of social skills among caregivers for the elderly is presented in Manuscript I. Based on a literature search using the major Psychology databases, nine studies (seven articles and two dissertations) were found, four about intervention evaluations and five reporting correlations for social skills with burden, stress, self-esteem, social support or quality of the relationship. According to the evidence, caregivers with a better-developed SS repertoire have more positive perceptions of their quality of life. In addition, although there are instruments to assess SS in other contexts, none were found for family caregivers of the elderly, in Brazil. Thus, it was concluded that it would be important to construct an instrument for this context, to assist in the identification of SS deficits, in this population. In Manuscript II, the objectives were to ascertain the primary conflicts that arise when caring for an elderly family member and identify the SS considered as important in this situation, to obtain information for preparing items for a new instrument. Interviews were conducted with 50 caregivers of the elderly, 25 elderly care-recipients and 25 professional in the field of aging. The main conflicts involved difficulties to reconcile differences of opinion, or financial issues. The SSs considered most useful included: expressing positive feelings, controlling aggressiveness, and discussing problems. Based on this information, 37 items were written, creating an initial version of an instrument to evaluate the social skills of those who care for elderly family members (IHS-CI). In Manuscript III, the aim was to describe the initial steps in the validation of this instrument. In Study 1, five independent judges conducted a semantic and content analysis of the instrument, resulting in the exclusion of six items. In Study 2, to obtain evidence about the psychometric properties of the new version of this instrument, 205 participants, all of whom cared for an elderly family member, completed the IHS-CI and a further five measures. Based on an analysis of the internal structure of the instrument, three factors were identified: Expression of emotions, Assertive communication, and Information seeking. The global, internal reliability of the instrument was excellent (α =0.886). Scores on the IHS-CI were positively correlated with greater quality of life and positive caregiver-elderly care-recipient interactions, and negatively correlated with burden, depression and conflicts. Additional studies are needed to gain further evidence of the validity of the IHSCI and to establish norms for the interpretation of test-scores. After this, the instrument will be ready for use to evaluate the social skills of family caregivers of the elderly, to guide interventions that can contribute to the greater wellbeing and quality of life of caregivers and of their elderly care-recipients.
Construction and psychometric analysis of a social skills Inventory for caregivers who assist an elderly family member
Keywords: Habilidades sociais; Cuidadores; Idosos; Psicometria; Sobrecarga; Social skills; Caregivers; Elderly; Psychometry; Burden; CIENCIAS HUMANAS::PSICOLOGIA